2007
DOI: 10.1680/geng.2007.160.4.185
|View full text |Cite
|
Sign up to set email alerts
|

Embankment supported on piles with biaxial geogrids

Abstract: The case study consists of a piled embankment built over a very soft, organic compressible clay layer 10 m deep. The height of the embankment supported on piles was about 1·3 m, and the piles, which measured 0·18 m × 0·18 m, were spaced 2·5 m apart in a square pattern, with 0·8 m wide square pile caps covered with a bidirectional 200 kN/m geogrid polyester reinforcement. A region of the piled supported embankment was instrumented to provide a better understanding of the overall embankment-reinforcement-pile ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(37 citation statements)
references
References 6 publications
0
35
0
2
Order By: Relevance
“…GR strain gauges ( in Figure 5.4) consisted of an ingenious system described by Almeida et al (2007) which measured the strain using strain gauges on a steel bar that had been attached with a reaction spring to the GR. …”
Section: Full-scale Test In Rio De Janeiromentioning
confidence: 99%
See 2 more Smart Citations
“…GR strain gauges ( in Figure 5.4) consisted of an ingenious system described by Almeida et al (2007) which measured the strain using strain gauges on a steel bar that had been attached with a reaction spring to the GR. …”
Section: Full-scale Test In Rio De Janeiromentioning
confidence: 99%
“…Seven full-scale cases have been reported with the data that will be considered in the present paper: in Brazil (Spotti, 2006;andAlmeida et al, 2007 and2008), in Houten, the Netherlands , near Woerden, the Netherlands ( , in Finland (Huang et al, 2009, including FDM calculations), in the Krimpenerwaard, the Netherlands (Haring et al, 2008), in Hamburg, Germany (Weirauch et al, 2013) and in France (Briançon and Simon, 2012). Additionally, four series of model experiments reported in the literature are considered in the present paper: from Virginia (Sloan, 2011 andMcGuire et al, 2012), the Republic of Korea (Oh and Shin, 2007), Germany (Zaeske, 2001, also reported in Kempfert et al, 2004) and the Netherlands (Van Eekelen et al, 2012a and b, adopted in Chapter 2 and 3 of this thesis).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Une analyse plus complète, avec une modélisation numérique des nappes, permettra de vérifier si la différence de transfert de charge observée peut être expliquée par la nature des géosynthétiques. Peu d'expérimentations en vraie grandeur permettent une analyse pertinente de ces mécanismes ; on citera cependant celles d 'Almeida et al (2007) ou Liu et al (2007) qui amènent à des observations semblables aux nôtres, en particulier sur : -l'influence de la réaction du sol compressible sur le tassement différentiel notamment lorsque la couche superficielle est de bonne qualité (Almeida et al, 2007) ; -le transfert de charge vers les inclusions rigides via une plate-forme granulaire renforcée et la répartition des tensions dans les nappes géosynthétiques (Liu et al, 2007).…”
Section: Identification Des Mécanismesunclassified
“…Results show that the existing methods generally lead to a conservative design; however, comparison between different approaches is recommended to optimise the design. Another case study of instrumented geogrid-reinforced and pile-supported embankment was presented in this journal by Almeida et al (2007); however, in that case the foundation soil consisted of highly compressible organic clay. Tarawneh et al (2018) propose a review of different traditional methods to predict settlements, by elaborating upon data collected by means of shallow foundation load tests on desert sand in Oman.…”
mentioning
confidence: 99%